CLOTBUST-Hands Free: Pilot Safety Study of a Novel Operator-Independent Ultrasound Device in Patients With Acute Ischemic Stroke - Barreto, Andrew D.; Alexandrov, Andrei V.; Shen, Loren; Sisson, April; Bursaw, Andrew W.; Sahota, Preeti; Peng, Hui; Ardjomand-Hessabi, Manouchehr; Pandurengan, Renganayaki; Rahbar, Mohammad H.; Barlinn, Kristian; Indupuru, Hari; et al. (Stroke (1970), 2013)
BACKGROUND AND PURPOSE—The Combined Lysis of Thrombus in Brain Ischemia With Transcranial Ultrasound and Systemic T-PA-Hands-Free (CLOTBUST-HF) study is a first-in-human, National Institutes of Health–sponsored, multicenter, open-label, pilot safety trial of tissue-type plasminogen activator (tPA) plus a novel operator-independent ultrasound device in patients with ischemic stroke caused by proximal intracranial occlusion. METHODS—All patients received standard-dose intravenous tPA, and shortly after tPA bolus, the CLOTBUST-HF device delivered 2-hour therapeutic exposure to 2-MHz pulsed-wave ultrasound. Primary outcome was occurrence of symptomatic intracerebral hemorrhage. All patients underwent pretreatment and post-treatment transcranial Doppler ultrasound or CT angiography. National Institutes of Health Stroke Scale scores were collected at 2 hours and modified Rankin scale at 90 days. RESULTS—Summary characteristics of all 20 enrolled patients were 60% men, mean age of 63 (SD=14) years, and median National Institutes of Health Stroke Scale of 15. Sites of pretreatment occlusion were as follows14 of 20 (70%) middle cerebral artery, 3 of 20 (15%) terminal internal carotid artery, and 3 of 20 (15%) vertebral artery. The median (interquartile range) time to tPA at the beginning of sonothrombolysis was 22 (13.5–29.0) minutes. All patients tolerated the entire 2 hours of insonation, and none developed symptomatic intracerebral hemorrhage. No serious adverse events were related to the study device. Rates of 2-hour recanalization were as follows8 of 20 (40%; 95% confidence interval, 19%–64%) complete and 2 of 20 (10%; 95% confidence interval, 1%–32%) partial. Middle cerebral artery occlusions demonstrated the greatest complete recanalization rate8 of 14 (57%; 95% confidence interval, 29%–82%). At 90 days, 5 of 20 (25%, 95% confidence interval, 7%–49) patients had a modified Rankin scale of 0 to 1. CONCLUSIONS—Sonothrombolysis using a novel, operator-independent device, in combination with systemic tPA, seems safe, and recanalization rates warrant evaluation in a phase III efficacy trial. CLINICAL TRIAL REGISTRATION—URLhttp://www.clinicaltrials.gov. Unique identifierCLOTBUST-HF NCT01240356.